Common genetic polymorphisms in pre-microRNAs and risk of bladder cancer. Issue 1 (December 2015) - Deng, Shi; Wang, Wei; Li, Xiang; Zhang, Peng
Abstract Background At present, inconsistent association between single nucleotide polymorphism (SNP) in pre-miRNAs (hsa-mir-196a2 rs11614913 C/T, hsa-mir-499 rs3746444 A/G, andhsa-mir-146a rs2910164 C/G) and bladder cancer were obtained in limited studies. We performed a case–control study to test whether these three common polymorphisms are associated with bladder cancer. One hundred fifty-nine patients affected by bladder cancer and 298 unrelated healthy subjects were enrolled in the study. Methods Using polymerase chain reaction–restriction fragment length polymorphism assay (PCR–RFLP), genotypes of these three SNPs were determined, and their associations with bladder cancer, as well as with clinic pathological factors, and tumor progression were analyzed. Results No association between bladder cancer risk and variant allele ofhsa-mir-196a2 rs11614913 C/T, hsa-mir-499 rs3746444 A/G, orhsa-mir-146a rs2910164 C/G was observed. Heterozygous genotype (CT genotype) of rs11614913 was associated with a significantly decreased bladder cancer risk (P = 0.004, OR = 0.56, 95 % CI = 0.38–0.83). Further stratified analyses showed that rs2910164 is associated with the tumor stage in a recessive model and with metastasis in a dominant model (P = 0.012, OR = 0.20, 95 % CI = 0.05–0.72 andP = 0.04, OR = 2.63, 95 % CI = 1.03–6.67, respectively). No association betweenhsa-mir-499 rs3746444 A/G and bladder cancer was observed. Conclusions Our results suggestedhsa-mir-196a2 rs11614913 C/T is associated with a significantly decreased risk of bladder cancer andhsa-mir-146a rs2910164 GG genotype is associated with clinical stage and metastasis in bladder cancer.